Pengembangan Flipbook “Ayo Sambung” untuk Mengenalkan Huruf Hijaiyah Bersambung pada Pembelajaran PAI Kelas 2 SD - Haslinda, Siti Nur; Nurmalasari, Nela; Mulyani, Sri; Aeni, Ani Nur (ISLAMIKA, 2024)
This article explains the use of the "Let's Connect" flipbook, a learning medium designed to make it easier for 2nd grade elementary school students to learn cursive hijaiyah letters in the context of Islamic Religious Education (PAI). This media is unique because it not only provides learning material about cursive hijaiyah letters, but also offers a series of questions in the form of games which aim to strengthen students' understanding of the material provided. The idea behind developing this media is to create a more interactive and interesting way of teaching, as well as helping teachers in packaging PAI learning materials. This research on media development follows the Design and Development (D&D) methodology using the ADDIE framework. The research was carried out by testing the use of the "Let's Connect" flipbook among grade 2 students at SDN Panyingkiran III. The results of this trial showed that this flipbook was effective in increasing students' understanding of cursive hijaiyah letters, as well as getting a positive response during the learning period.